2020
DOI: 10.18632/aging.103231
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptor affects the response to immune checkpoint therapy by suppressing PD-L1 in hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is a heterogeneous malignancy with gender-related differences in onset and course. Androgen receptor (AR), a male hormone receptor, is critical in the initiation and progression of HCC. The role of AR in HCC has been mechanistically characterized and anti-AR therapies have been developed, showing limited efficacy. Immunotherapy targeting immune checkpoint proteins may substantially improve the clinical management of HCC. The mechanism by which AR influences HCC immune state remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 44 publications
0
22
0
Order By: Relevance
“…Similar to Jiang et al (2020), we identified a direct interaction between AR and the CD274 gene body using CUT&Tag. However, since we were able to profile AR binding sites genome-wide, we also identified an AR binding signal at the NFKBIA promoter.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Similar to Jiang et al (2020), we identified a direct interaction between AR and the CD274 gene body using CUT&Tag. However, since we were able to profile AR binding sites genome-wide, we also identified an AR binding signal at the NFKBIA promoter.…”
Section: Discussionmentioning
confidence: 88%
“…To our knowledge, this is the first study identifying a relationship between AR activity and PD-L1 expression in thyroid cancer. Recently, Jiang et al (2020) characterized AR suppression of PD-L1 in hepatocellular carcinoma. In combination, these findings point to a previously unappreciated role AR has on PD-L1 expression in multiple tissue types and, given that the PD-1/PD-L1 axis is an actionable immunotherapeutic target for various cancers, indicate that AR activity can impact the response to immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with advanced HCC are at substantial risk of death, and chemotherapy remains unsatisfied with a survival benefit. Evidence has proved the potential of immune checkpoint inhibitors (ICIs) in HCC treatment [ 8 , 35 37 ]. However, only a small portion of HCC patients achieved a therapeutic effect from ICIs.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical evidence has suggested a potential therapeutic synergy by combining AR modulation and PD-1 blockade. Androgens are immunosuppressive and target both innate and adaptive immune systems to dampen the immune response [28][29][30][31][32][33][34]. Inhibition of AR sensitizes cancer cells to immunemediated killing.…”
Section: Investigator's Assessmentmentioning
confidence: 99%
“…Inhibition of AR sensitizes cancer cells to immunemediated killing. AR suppresses PD-L1 expression by binding to the PD-L1 promotor and directly attenuating PD-L1 gene transcription [29,30]. In addition, AR signaling inhibits thymocyte production [31], whereas AR blockade has been shown to increase naive T cell generation resulting in a larger diversity of T cell repertoire that could potentially respond to PD-1 blockade [32,33].…”
Section: Investigator's Assessmentmentioning
confidence: 99%